A Pilot Study of Automated Pupillometry in the Treatment of Opioid Use Disorder. Issue 6 (November 2021) - Peeler, Crandall E.; Gorgy, Merit; Sadlak, Natalie; Sathe, Shaleen; Tamashunas, Nina; Fiorello, Marissa G.; Cabral, Howard; Paasche-Orlow, Michael K.; Weinstein, Zoe M.
Abstract : Introduction/Background: A rough, visual estimate of pupil size is used in grading the severity of opioid withdrawal. Few studies have examined the clinical utility of more precise automated pupillometry measurements. Methods: This prospective cohort study enrolled 27 patients receiving opioid agonist therapy (OAT) to treat cravings or withdrawal during an acute hospitalization. Six sets of automated pupillometry measurements were obtained at regular intervals before and after administration of OAT. Clinical Opiate Withdrawal Scale measurements were performed pre and post OAT. Primary outcomes included pupil size in dark and bright illumination (mm). Latency of the pupillary light response (s), constriction and dilation velocity (mm/s), and percent constriction (%) were secondary outcomes. Results: The mean predosing pupil size in dark and bright illumination was 4.33 ± 1.40 mm and 2.96 ± 0.79 mm, respectively. A significantly decreased mean pupil size was first detected at 15 minutes postdosing (4.01 ± 1.34 mm, P = 0.0115 for dark illumination; 2.71 ± 0.72 mm, P = 0.0003 for bright illumination) and this reduction in pupil size persisted at later postdosing timepoints. Those with Clinical Opiate Withdrawal Scale <5 after dosing had a greater decrease in dark pupil size (10.6% ± 13.2 vs 3.2% ± 3.2, P = 0.043). There was no significant change in the remaining pupil reactivity parameters. Conclusions: Automated pupillometry demonstrated a small but significant change in mean pupil size that occurred within 15 minutes of OAT dosing and was associated with low withdrawal scores. This pilot may inform future work to incorporate pupillometry measurement into OAT dosing assessments. Abstract : Supplemental Digital Content is available in the text